PLASMID PROFILING AND CURING OF MULTIDRUG RESISTANT ESCHERICHIA COLI RECOVERED FROM RETAIL CHICKEN MEAT - M. Gohar; A. A. Sheikh; A. A. Anjum; T. Hussain; J. Muhammad; A. Tabbassum; A. Kanwal; I. Safdar (Journal of Animal and Plant Sciences, 2015)
Confirmed E. coli (n = 25) were analyzed for the presence of plasmids and cured using temperature and sodium dodecyl sulphate (SDS) treatments. Plasmid profiling of the isolates showed that 96 % isolates were harboring plasmids of varying size and number. The average plasmid number among the isolates was 2.28, ranging from 0 – 5 plasmids per isolate and plasmid size varied from 100bp – 12kb which was distributed randomly in these isolates. Statistically no significant correlation (p>0.05) was found between antibiotic resistance and plasmid profiles. Plasmid curing study showed 3.9% and 16.7% curing efficiency with that of temperature and SDS treatment, respectively. Statistical analysis revealed that resistant isolates, treated with either physical or chemical treatments produced significant results (p<0.05) of plasmid curing. Antimicrobial resistance genes might be located on plasmid and statistically no relationship was observed between antibiotic resistance and plasmid profiles.
Keywords: Plasmid profiles; plasmid curing; E. coli; antibiotic resistance